Positivisasi Hukum Keluarga Islam sebagai Langkah Pembaharuan Hukum Islam di Indonesia: Kajian Sejarah Politik Hukum Islam - Ma'rifah, Nurul (Al-Manahij: Jurnal Kajian Hukum Islam, 2019)
This paper discusses the making Islamic family law a formal law in the perspective of the political history of Islamic law in Indonesia, which cannot be separated from the role of the regime since the beginning of the Old Order era. In this era, the regime showed its alignment with the renewal of Islamic law. However, when the regime was not as firm and tended to be democratic, as it was during the Reformation era, Islamic family law reform tended to be stagnant. On the other hand, the history of Islamic family law renewal also experienced ups and downs because it is affected by political configurations, in which Indonesian Muslims attitudes could be classified into progressive and Islamist groups. Progressive groups try to fight for the renewal of Islamic family law contextually; whereas Islamist groups are more textual in responding to Islamic family law reform.